Legislative Defections and Democratization in Nigeria - Ayedogbon, Gbenga Sola; Falade, Bunmi .A. (Kashere Journal of Politics and International Relations, 2025)
The paper examines the phenomenon of legislative/party defection in Nigeria, underscoring the historical dimensions of the problem, conceptual and theoretical issues of party defection, defections in the 2015 elections, and predisposing factors of legislative defection/carpet crossing in Nigeria. The paper submits that the problem of legislative defection/carpet crossing is deep rooted such that they cannot, in their present form and character, midwife successful democratization in Nigeria. Some of its notable causes include the poverty of political party ideology and poor institutionalisation of political parties; the form and character of the post-colonial state, constitutional ambiguities regarding carpet crossing, primacy of political power and politics of patronage, among others. Consolidating Nigeria’s democracy demands that the roots of these contradictions are adequately redressed.